Assessing Learner Autonomy in Moroccan Higher Education: Toward a Localized Measurement Scale - Khabar, Fatima Zahrae; AZHAR, Adil (International Journal of Language and Literary Studies, 2025)
Learner autonomy has become one of the central goals of education worldwide. To support this goal, it is crucial to measure how autonomous learners are and identify the factors that help or limit its development. Although some instruments exist, many are limited in scope, and they are rarely adapted to local contexts. In Morocco, despite the emphasis on autonomy in the educational policies, no scale has been developed to measure it. This article presents the development of a localized Learner Autonomy Measurement Scale (LAMS) for the Moroccan context. The scale is based on three major frameworks: Benson’s (1997, 2001) multidimensional model, Nunan’s (1997) developmental stages, and Tassinari’s (2012) dynamic model. It consists of thirty items across nine indicators, using a 5-point Likert scale, and is designed to capture autonomy as a multidimensional, developmental, and dynamic construct. This article presents the conceptual development and theoretical grounding of a localized scale to measure learner autonomy, providing a foundation for future empirical validation